Implementation of 4C skills through problem solving: a study among mathematics teachers in Malaysia - Noor Nasran, Nik Abdul Hadi; Zakaria, Mohamad Ikram (Journal of Education and Learning (EduLearn), 2025)
In the current realm of education 4.0, teachers play a pivotal role as facilitators of holistic skill development. The shift in focus towards accentuating creativity, communication, critical thinking and collaboration (4C) skills signifies an acknowledgment of the changing demands brought about by the industrial revolution 4.0. This transformation in educational approaches contributes significantly to the collective adaptability and innovative potential of succeeding generations. Against this backdrop, this study was conducted to investigate how mathematics teachers in Malaysia implement the 4C skills, specifically through problem-solving. The study applied a survey method involving 250 mathematics teachers in Malaysia. Data were collected using a questionnaire, meanwhile, descriptive statistics were used to analyze and present the research data. Overall, the study’s outcomes revealed that mathematics teachers exhibit adeptness in effectively integrating the 4C skills within the context of problem-solving. However, the study also brought to light challenges encountered by mathematics teachers, particularly in the realm of creative teaching, especially when incorporating technology. These identified challenges resonate with broader concerns in the educational landscape, underscoring the imperative for robust support systems, continual professional development initiatives, and a transformative shift in the educational paradigm towards embracing innovative teaching methodologies.